A novel melatonin‐regulated lncRNA suppresses TPA‐induced oral cancer cell motility through replenishing PRUNE2 expression. Issue 3 (26th August 2021) - Su, Shih‐Chi; Yeh, Chia‐Ming; Lin, Chiao‐Wen; Hsieh, Yi‐Hsien; Chuang, Chun‐Yi; Tang, Chih‐Hsin; Lee, Yi‐Chan; Yang, Shun‐Fa
Abstract: The inhibitory effect of melatonin on cancer cell dissemination is well established, yet the functional involvement of lncRNAs in melatonin signaling remains poorly understood. In this study, we identified a melatonin‐attenuated lncRNA acting as a potential melatonin‐regulated oral cancer stimulator (MROS‐1). Downregulation of MROS‐1 by melatonin suppressed TPA‐induced oral cancer migration through replenishing the protein expression of prune homolog 2 (PRUNE2), which functioned as a tumor suppressor in oral cancer. Melatonin‐mediated MROS‐1/PRUNE2 expression and cell motility in oral cancer were regulated largely through the activation of JAK‐STAT pathway. In addition, MROS‐1, preferentially localized in the nuclei, promoted oral cancer migration in an epigenetic mechanism in which it modulates PRUNE2 expression by interacting with a member of the DNA methylation machinery, DNA methyltransferase 3A (DNMT3A). Higher methylation levels of PRUNE2 promoter were associated with nodal metastases and inversely correlated with PRUNE2 expression in head and neck cancer. Collectively, these findings suggest that MROS‐1, serving as a functional mediator of melatonin signaling, could predispose patients with oral cancer to metastasize and may be implicated as a potential target for antimetastatic therapies.